2018
DOI: 10.1017/s0950268818001899
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of Pseudomonas aeruginosa in culture positive otitis externa in South East England

Abstract: Otitis externa is the inflammation of the external auditory canal. The disease is common and shows a seasonal variation with a greater incidence in warmer months. Pseudomonas aeruginosa is a common pathogen in otitis externa and in this retrospective study, we show a corresponding seasonal variation in the proportional incidence of P. aeruginosa isolates from otitis externa in South East England. In total 7770 patients were diagnosed with otitis externa over a period of 9 years from January 2008 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Harvesting the samples and freezing them in À728C until thawing for DNA extraction functioned expectedly, as most samples yielded sufficiently data and had low proportion of suspected contaminants. There is also likely to be some seasonal variation in the microbial community, and earlier studies have shown such variation in acute otitis externa (42). Unfortunately, the seasonal variation of the healthy EAC microbiota could not be confirmed in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Harvesting the samples and freezing them in À728C until thawing for DNA extraction functioned expectedly, as most samples yielded sufficiently data and had low proportion of suspected contaminants. There is also likely to be some seasonal variation in the microbial community, and earlier studies have shown such variation in acute otitis externa (42). Unfortunately, the seasonal variation of the healthy EAC microbiota could not be confirmed in this study.…”
Section: Discussionmentioning
confidence: 57%
“…The development of AOE infection is correlated with an alkaline shift of the normal acidic pH of the outer ear canal (10). The incidence of AOE also increases significantly during the summer, due to high temperatures and humidity (11) otitis externa, reported that infection was seen most frequently in August and September and least frequently in April and May (12). In our study, our cases of AOE occurred most frequently during the summer and least frequently during the spring, with July being the month with the highest number of AOE diagnoses (18 cases; 23.6%) and May being the month with the fewest (1 case; 1.3%).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a correlation between the development of otitis and swimming in water contaminated with the bacteria P. aeruginosa has been recorded [11,12]. There is also proof that otitis is directly connected with the presence of moisture [13]. There are factors that boost the rapid growth of P. aeruginosa.…”
Section: Introductionmentioning
confidence: 94%